Does Social Management Process Matter? - Elok Fitriya; Bambang Tjahjadi (Universitas Muhammadiyah Malang, 2024)
Purpose: The aim of this research is to find out whether social environment is a mediating variable in the influence of the main director's structure on management performance. Methodology/approach: The method used in this research is a qualitative research method sourced from secondary data collected by researchers through OSIRIS data from 709 companies whose shares are publicly traded on the Indonesia Stock Exchange. Findings: The findings show that the influence of the composition of the board of directors on company performance varies greatly among social environments. Practical Implications: This research adds to research references on the influence of governance on performance which is moderated by the company's social environment. Originality/value: the novelty in this research is adding a new variable, namely the social environment as a mediating variable.